Two-dimensional nanovermiculite and polycaprolactone electrospun fibers composite scaffolds promoting diabetic wound healing - Huang, Xingtai; Wang, Qirui; Mao, Runyi; Wang, Zeying; Shen, Steve G.F.; Mou, Juan; Dai, Jiewen (Journal of nanobiotechnology, 2022)
Promoting diabetic wound healing is still a challenge, and angiogenesis is believed to be essential for diabetic wound healing. Vermiculite is a natural clay material that is very easy to obtain and exhibits excellent properties of releasing bioactive ions, buffering pH, adsorption, and heat insulation. However, there are still many unsolved difficulties in obtaining two-dimensional vermiculite and using it in the biomedical field in a suitable form. In this study, we present a versatile organic-inorganic composite scaffold, which was constructed by embedding two-dimensional vermiculite nanosheets in polycaprolactone electrospun fibers, for enhancing angiogenesis through activation of the HIF-1[alpha] signaling pathway and promoting diabetic wound healing both in vitro and in vivo. Together, the rational-designed polycaprolactone electrospun fibers-based composite scaffolds integrated with two-dimensional vermiculite nanosheets could significantly improve neo-vascularization, re-epithelialization, and collagen formation in the diabetic wound bed, thus promoting diabetic wound healing. This study provides a new strategy for constructing bioactive materials for highly efficient diabetic wound healing.